Economic Development, Novelty Consumption, and Body Weight: Evidence from the East German Transition to Capitalism - Davide Dragone; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2015)
This paper develops a conceptual framework that can explain why economic development goes along with increases in body weight and obesity rates. We first introduce the concept of novelty consumption, which refers to an increase in food availability due to trade or innovation. Then we study how novel food products alter the optimal consumption bundle and welfare, and possibly lead to changes in body weight. We test our model employing the German reunification as a fast motion natural experiment of economic development. Our data elicit detailed information on East Germans' food consumption, body mass, and diet-related health. After the fall of the Wall, East Germans permanently changed their diet by consuming novel western food products. A significant population share permanently gained weight. This is consistent with our theoretical framework where past affects current consumption, and where novel goods determine consumption changes over time with ambiguous effects on diet-related health.
Keywords: D11; D12; I12; I15; L66; O10; O33; Q18; R22; 330; economic development; food consumption; habit formation; learning; novel goods; obesity; nutrition-related health; German reunification